Synthesis of Ruddlesden-Popper Sr2Co0.75Ni0.25O4 compound and investigating some of its physical properties (Latakia University Journal -Basic Sciences Series, 2023)
In this paper the Ni-doping effect on structure and electrical properties of Ruddlesden-Popper Sr2CoO4: n=1 have been investigated for the first time. The synthesis conditions of novel Sr2Co0.75Ni0.25O4 compound have been determined and investigated, The conventional ceramic method were obliged at 1100°c temperature for 6 hours and according to structural study of XRD pattern, co-phases were noticed owing to the incomplete decomposition of strontium carbonate and additionally another phases of strontium and cobalt were found, by elevating the system temperature to 1250°c a melting event were noticed, therefor  Sol-Gel Citrate Nitrate Gel method was obliged for obtaining single phase at relatively low-temperature 1050°c for 96 hours heating duration, the major role Co3O4 plays in the course of reaction have been notified, and by investigating the electrical properties by measuring the disc resistivity to AC in the range -0.5 ـــ +0.5)v) it was found that it has a good dielectric properties and by measuring the electrical capacitance at 1kH it was found that the disc had a good capacitance value, good relative dielectric constant, and low loss tangant.